Alphabetized Co-Authorship in Economics Reconsidered - Klaus Wohlrabe; Lutz Bornmann (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this article, we revisit the analysis of Laband and Tollison (2006) who documented that articles with two authors in alphabetical order are cited much more often than non-alphabetized papers with two authors in the American Economic Review and the American Journal of Agricultural Economics. Using more than 120,000 multi-authored articles from the Web of Science economics subject category, we demonstrate first that the alphabetization rate in economics has declined over the last decade. Second, we find no statistically significant relationship between alphabetized co-authorship and citations in economics using six different regression settings (the coefficients are very small). This result holds when accounting for intentionally or incidentally alphabetical ordering of authors. Third, we show that the likelihood of non-alphabetized co-authorship increases the more authors an article has.
Keywords: A12; A14; 330; alphabetization; co-authorship; citations; Web of Science